Tipologia, geometria e cronologia da tectônica vinculada ao Vulcano-plutonismo fissural paleoproterozóico da região de São Félix do Xingu (PA), Cráton Amazônico - SOUSA, Luís Kennedy Andrade (2020)
The Amazonian Craton in the late Paleoproterozoic, was the scene of intense effusive and explosive volcanism, identified as Uatumã event. It contains a large volume of granitoids and intermediate and felsic volcanic rocks, with subordinate mafic plutonic types. Although the investment in geological studies in the region in recent years there is still lack of geological data, geochemical and structural assist in more detailed knowledge of the evolution of the volcanic rocks, both in the region near the town of São Félix do Xingu, as compared to the Craton as a whole. The work consists of a study in classic structural geology, taking as reference the volcanic rocks of the Paleoproterozoic Sobreiro Formation and Iriri Formation, sitting unconformably on Archean basement rocks of the Carajás region. Aims to obtain data structures in the context of volcanic rocks to the development of structural models that associated with existing petrological data, enabling a breakthrough in the understanding of this crustal segment Amazon. The data presented in this work, referring to the rocks in the region of São Félix do Xingu, suggest a model with two deformational episodes: the first transpressive, ductile character, and the second transtensivo brittle character, which explains the geometric layout and spatial arrangement of rocks observed.